Tekanan Ekonomi Dan Pengabaian Anak : Dampak Judi Online Terhadap Kesejahteraan Anak Usia Dini - Rifa Farhanatul Kamilah; Risbon Sianturi; Taopik Rahman (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to analyze the impact of online gambling on financial strain within families and its implications for the well-being of young children. The increasing prevalence of online gambling in society not only affects household financial stability but also influences the quality of parenting experienced by children. This study employs a literature review method by examining various relevant scholarly sources related to child well-being, economic pressure, and parental addictive behaviors. The findings indicate that parental involvement in online gambling can lead to economic instability within the family, thereby increasing the risk of neglecting children’s basic needs, both physically and emotionally. Such conditions have significant implications for early childhood well-being, including physical health, socio-emotional development, and a sense of security. Moreover, elevated financial stress can adversely affect parent–child interactions, resulting in less effective parenting practices. Based on these findings, it is crucial for multiple stakeholders, including families, educators, and policymakers, to enhance awareness of the detrimental effects of online gambling and to promote the establishment of a supportive environment that fosters the well-being of young children